1982
DOI: 10.1590/s0100-83581982000200002
|View full text |Cite
|
Sign up to set email alerts
|

Controle de azevém (Lolium multiflorum L.), e gorga (Spergula arvensis L.) e seletividade de herbicidas as culturas de trigo, cevada e centeio

Abstract: Foram realizados três experimentos a campo em 1980, no Centro Nacional de Pesquisa de Trigo/EMBRAPA, Passo Fundo, RS, visando conhecer o comportamento dos herbicidas diclofop, dicamba, a associação 2,4 D com dicamba e a mistura diclofop + (2,4 D + dicamba), no controle de azevém (Lolium multiflorum L.) e gorga (Spergula arvensis L.). Ao mesmo tempo foi avaliada a seletividade que estes herbicidas apresentam às culturas de trigo (Triticum aestivum L.), cevada (Hordeum vulgare L.) e centeio (Secale cereale L.). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Trezzi et al (2007) observed the antagonistic effect of mixing clonadifoppropargyl + 2,4-D (20 670 g ha -1 ) in control of ryegrass (Lolium mutiflorum) regarding the application of the graminicide isolated, as well as higher rates of control with the mixture as the clonadifop-propargyl concentration was increased. As to Velloso & Dal'piaz (1982), they reported the existence of incompatibility mixture diclofop + dicamba + 2,4-D (720 + 576 + 97 g ha -1 ) used in the control of ryegrass (Lolium mutiflorum) and Gorga (Spergula arvensis) on wheat, barley and rye.…”
Section: Resultsmentioning
confidence: 99%
“…Trezzi et al (2007) observed the antagonistic effect of mixing clonadifoppropargyl + 2,4-D (20 670 g ha -1 ) in control of ryegrass (Lolium mutiflorum) regarding the application of the graminicide isolated, as well as higher rates of control with the mixture as the clonadifop-propargyl concentration was increased. As to Velloso & Dal'piaz (1982), they reported the existence of incompatibility mixture diclofop + dicamba + 2,4-D (720 + 576 + 97 g ha -1 ) used in the control of ryegrass (Lolium mutiflorum) and Gorga (Spergula arvensis) on wheat, barley and rye.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, corn spurry (Spergula arvensis L.) was practically absent in the first 4 yr, but its populations increased rapidly in the second half of the study (Figure 2D). This weed is usually sufficiently controlled with several of the herbicides used in the experiment, such as glyphosate (Ivany 2004), dicamba (Velloso and Dal'Piaz 1982), and pendimethalin (Haar et al 2001). Spergula arvensis is a summer annual species that can also behave as a winter annual, depending on location and due to seed dimorphism creating variable dormancy levels (Wagner 1988).…”
Section: Weed Population Trajectoriesmentioning
confidence: 99%